PENINGKATAN PENDAPATAN UKM PADA HACORD GALLERY DENGAN APLIKASI WEB MARKETPLACE E-COMMERCE - Sunarti, Sunarti; Rachmawati, Susan; Handayanna, Frisma (Jurnal Terapan Abdimas, 2019)
Abstract. Hacord Gallery is a central shop for souvenirs in Depok. The product that is marketed is the production of the Small and Medium Enterprises (UKM) of Depok city, already has permits, proper packaging, and the best quality products. More than 50 SMEs market their products such as types of fashion, crafts, souvenirs, craft, frozen food, food, beverages, and herbal medicines. The problem is marketing activities using conventional systems. By recording, both sales and purchase transactions in a book, promotion using brochures, financial management using a calculator and the quality of human resources is still low in education. Limited access to information and low competitiveness due to lack of information technology support and expensive internet access. Solutions to deal with problems are built by e-commerce marketplace applications. E-Commerce a website makes Hacord Gallery a center for souvenirs in the city of Depok and known by the public. The method in this service is a learning by doing method, starting from field surveys to evaluating training results. The training was conducted by giving information on the use of e-commerce applications to increase sales and income, mentoring was carried out using the application process while discussions were carried out by the service team and partners. The results of this activity in the form of e-commerce marketplace applications provide goods buying and selling services so as to create business opportunities for SMEs in marketing their products. To ensure the success of this program, an evaluation will be carried out at each stage of program development. Abstrak.Hacord Gallery merupakan toko pusat oleh-oleh kota Depok. Produk yang dipasarkan adalah produksi Usaha Kecil dan Menengah (UKM) kota Depok, sudah memiliki izin, kemasan layak dan kualitas produk terbaik. Lebih dari 50 UKM memasarkan produknya seperti jenis fashion, kerajinan, souvenir, craft, frozen food, makanan, minuman, dan jamu herbal. Permasalahannya adalah kegiatan pemasaran menggunakan sistem konvensional. Dengan melakukan pencatatan, baik transaksi penjualan ataupun pembelian ke dalam sebuah buku, promosi menggunakan brosur, pengelolaan keuangan menggunakan kalkulator dan kualitas sumber daya manusia masih rendah pendidikannya. Terbatasnya akses informasi dan rendahnya daya saing disebabkan kurangnya dukungan teknologi informasi dan mahal akses internet. Solusi untuk menangani permasalahan maka dibangun aplikasi marketplace e-commerce. E-Commerce sebuah website menjadikan Hacord Gallery sebagai pusat oleh-oleh dikota Depok dan dikenal masyarakat. Metode dalam pengabdian ini adalah metode learning by doing, di mulai dari survei lapangan sampai pada evaluasi hasil pelatihan. Pelatihan dilakukan dengan memberi informasi penggunaan aplikasi e-commerce untuk meningkatkan penjualan dan pendapatan, pendampingan dilakukan proses penggunaan aplikasi sedangkan diskusi dilakukan tim pengabdian dan mitra. Hasil kegiatan ini berupa aplikasi marketplace e-commerce menyediakan layanan jual beli barang sehingga menciptakan peluang bisnis para UKM dalam memasarkan produknya. Untuk menjamin keberhasilan program ini maka akan dilakukan evaluasi pada setiap tahapan perkembangan program.